The Coiled-Coil Domain of the Adenovirus Type 5 Protein IX Is Dispensable for Capsid Incorporation and Thermostability - Vellinga, Jort (American Society for Microbiology, 2005)
The 14.4-kDa hexon-associated protein IX (pIX) acts as a cement in the capsids of primate adenoviruses and confers a thermostable phenotype. Here we show that deletion of amino acids 100 to 114 of adenovirus type 5 pIX, which eliminates the conserved coiled-coil domain, impairs its capacity to self-associate. However, pIXΔ100-114 is efficiently incorporated into the viral capsid, and the resulting virions are thermostable. Deletion of the central alanine-rich domain, as in pIXΔ60-72, does not impair self-association, incorporation into the capsid, or the thermostable phenotype. These data demonstrate, first, that the self-association of pIX is dispensable for its incorporation into the capsid and generation of the thermostability phenotype and, second, that the increased thermostability results from pIX monomers binding to different hexon capsomers rather than capsid stabilization by pIX multimers.